Resilience as a Mediator of Peer Support Against Workforce Burnout - Wulansari, Resi; Dimala, Cempaka Putrie; Ibad, M Choirul (Psikoborneo: Jurnal Ilmiah Psikologi, 2023)
The reduced number of employees caused by the effects of the Covid-19 pandemic has caused the workload of employees who are still working to increase, so that employees experience burnout. The purpose of this study was to determine whether the influence of coworker support on burnout, the influence of coworker support on resilience, the effect of resilience on burnout and the influence of coworker support on burnout with resilience as the mediator. The research subjects are workers who are domiciled in Karawang, the number of respondents is 400 people taken using the incidental sampling technique. This study uses a quantitative approach. Questionnaires were distributed via Google form. The burnout scale using the adaptation scale from the Maslach Burnout Inventory-Human Service Survey (MBI-HSS) which consists of 11 question items, the peer support scale using the adaptation scale from Sarafino & Smith theory which consist of 20 question items, the resilience scale uses the adaptation scale from Connor David’s Resilience Scale (CD-RISC), which consists of 23 items questions. Data analysis using simple regression and multiple regression. The influence of coworker support variables on burnout is 19.1%. The influence of peer support on resilience is 4.7%. The effect of resilience on burnout. The effect of resilience on burnout is 24.2%. The influence of the mediator using the Sobel calculator with a value of 3.98. Based on the results of statistical tests conducted, there is a significant positive effect of coworker support on resilience, there is a significant negative effect of coworker support on burnout, there is a significant negative effect of resilience on burnout, there is a mediator effect of the resilience between coworker support on burnout.Pengurangan jumlah karyawan yang disebabkan oleh efek pandemi covid-19 menyebabkan beban kerja karyawan yang masih bekerja bertambah, sehingga karyawan mengalami burnout. Tujuan penelitian ini adalah untuk mengetahui apakah terdapat pengaruh dukungan rekan kerja terhadap burnout, pengaruh dukungan rekan kerja terhadap resiliensi, pengaruh resiliensi terhadap burnout dan pengaruh dukungan rekan kerja terhadap burnout dengan resiliensi sebagai mediator nya. Subjek penelitian merupakan tenaga kerja yang berdomisili di Kabupaten Karawang, jumlah responden sebanyak 400 orang diambil menggunakan teknik Incidental sampling. Penelitian ini menggunakan pendekatan kuantitatif. Kuesioner di sebar melalui Google form. Skala burnout menggunakan skala adaptasi dari Masclach Burnout Inventory-Human Service Survey (MBI-HSS) yang terdiri dari 11 aitem pertanyaan, skala dukungan rekan kerja menggunakan skala adaptasi dari teori Sarafino & Smith yang terdiri dari 20 aitem pertanyaan, skala resiliensi menggunakan skala adaptasi dari Connor-Davidson’s Resilience Scale (CD-RISC), yang terdiri dari 23 aitem pertanyaan. Analisis data menggunakan regresi sederhana dan regresi berganda. Besar pengaruh variabel dukungan rekan kerja terhadap burnout sebesar 19.1%. Besar pengaruh dukungan rekan kerja terhadap resiliensi sebesar 4.7%. Besar pengaruh resiliensi terhadap burnout sebesar 24.2%. Besar pengaruh mediator menggunakan kalkulator sobel dengan nilai sebesar 3.98. Berdasarkan hasil uji statistik yang dilakukan terdapat pengaruh positif signifikan dukungan rekan kerja terhadap resiliensi, terdapat pengaruh negatif signifikan dukungan rekan kerja terhadap burnout, terdapat pengaruh negatif siginifikan resiliensi terhadap burnout, terdapat pengaruh mediator resiliensi antara dukungan rekan kerja terhadap burnout.